2016
DOI: 10.4102/ojvr.v83i1.1040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Theileria</i> and <i>Babesia</i> species in Tunisian sheep

Abstract: In this study, the prevalence of Theileria and Babesia species in sheep was assessed with Giemsa-stained blood smear examination and polymerase chain reaction to identify the different piroplasms in 270 sheep from three Tunisian bioclimatic zones (north, centre, and south). The overall infection prevalence by Babesia spp. and Theileria spp. in Giemsa-stained blood smears was 2.9% (8/270) and 4.8% (13/270) respectively. The molecular results showed that sheep were more often infected by Theileria ovis than Babe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
1
Order By: Relevance
“…The higher prevalence obtained in the work of Rjeibi et al. (2016) could be attributed to the sampling location. In fact, authors identified the different piroplasms from three Tunisian bioclimatic zones (north, centre, and south) and they found that Babesia ovis was found exclusively in sheep from the centre of Tunisia whereas Theileria ovis was found in all regions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The higher prevalence obtained in the work of Rjeibi et al. (2016) could be attributed to the sampling location. In fact, authors identified the different piroplasms from three Tunisian bioclimatic zones (north, centre, and south) and they found that Babesia ovis was found exclusively in sheep from the centre of Tunisia whereas Theileria ovis was found in all regions.…”
Section: Discussionmentioning
confidence: 68%
“…The overall prevalence of Babesia and Theileria infection was 4.21%. This prevalence was compared to values in the study of Rjeibi, Darghouth, and Gharbi (2016) by PCR which reached 16.3 and 7.8% for Theileria ovis and Babesia ovis respectively. The higher prevalence obtained in the work of Rjeibi et al.…”
Section: Discussionmentioning
confidence: 87%
“…infection has been documented among sheep in Kurdistan Region of Iraq of [3]. Jatau et al [22], Rjeibi et al [8], Bilgic et al [4], and Mohammed et al [23] reported a higher prevalence of hemoparasites infections among sheep in Nigeria, Tunisia, Turkey, and Sudan, respectively. Disparity in time of study, breeds of animals sampled, differences in sample size, the diagnostic tool used, and the management and nutritional status of animals sampled could have resulted in the inconsistency of prevalence recorded in this study compared to those by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…A. phagocytophilum affects both cattle and sheep [4,7]. Babesiosis is a tick-borne hemoparasitic disease caused by numerous species of protozoa from the genus Babesia [8]. These protozoans are found in the erythrocyte, and can infect a wide range of domestic and wild animals, and occasionally man [9].…”
Section: Introductionmentioning
confidence: 99%
“…were detected in 31 animals out of 45 (68.9%) by ME, which was similar to the rate reported by Gadelrb [19] in Khartoum State, Central Sudan (68%) but higher than that found by Osman et al [20], South-Darfur State, western, Sudan (4.9%). Different prevalence rates were recorded in different parts of the world; 29% in Iran [21], 4.8% in Tunisia [22] and 1.2% in Maghreb [23]. The high prevalence rate determined in the current study compared to other regions may be attributed to differences in climatic conditions and sample collection times as observed by Yaghfoori [24].…”
Section: Discussionmentioning
confidence: 48%